Restorasi pada gigi anterior setelah perawatan endodontik Restoration of anterior tooth after endodontic treatment - Besse Tenri Awaru; Juni Jekti Nugroho (Journal of Dentomaxillofacial Science, 2012)
Structure of the anterior teeth after endodontic treatment usually become weak because of the extensive loss of toothstructure. It causes a big problem to an endodontically treatment tooth when considering its restoration, examplereduced strength of the remaining tooth structure. Restoration that covers the tooth crown can be used if aesthetic andfunctional problems factors have been considered. However, composite resins are also often the treatment of choice forthe restoration of endodontically treated tooth. In this literature review, it will be discussed the selection of the properrestoration of the anterior teeth that have been endodontically treated.